Penatalaksanaan kista dentigerous pada anak - Rahardjo . (Makassar Dental Journal, 2018)
Dentigerous cyst is a cyst that develops from the tooth-forming epithelium. These cysts usually involve unerupted teeth. Dentigerous cysts are usually found in incisor and canines teeth area on the upper jaw. In the lower jaw usually involves the unerupted third molar tooth area. Dentigerous cysts in children can lead to impaired bone growth of the jaw and teeth. The cause of this cyst can be due to an infection and inflammation during childhood and also due to lack of nutrition during the growth and development of bones and teeth. Case 1. A 12-year-old boy with a bump on the left anterior region and changed position of the maxillary incisors; there was no pain and there was crepitus on palpation. In orthopanoramic rontgen there was a canine that do not erupt, covered with radiolucent area firm boundaries. Case 2. A 16-year-old woman with a bump in the left lower jaw. There was no pain, there was crepitus on palpation, and the orthopanoramic rontgen there was well defined radiolucent area involving unerupted third molar. Both cases are expressed as a dentigerous cyst. Dentigerous cyst treatment depends on the location, size, and age of the patient. Basically the treatment aims to maintain the growth and development of facial bone and tooth development. Marsupialisation and enucleation is the treatment of cysts in general. In both cases performed two consecutive actions that were marsupialisation and enucleation. It was concluded that marsupialisation and continued with enucleation, the results were satisfactory, growth disorder of the facial bones and teeth can be avoided.